Subconjunto terminológico CIPE® para a pessoa acometida pelo infarto agudo do miocárdio - Passinho, Renata Soares (2017)
Introduction: Acute myocardial infarction (AMI) is conceptualized as the death of cardiomyocytes due to prolonged ischemia. The present study deals with the elaboration of the terminological subset of the International Classification for Nursing Practice (CIPE®), specific for attending to the person affected by AMI. Objectives: To elaborate and validate the terminology subset of the International Classification for Nursing Practice - CIPE® for the person with acute myocardial infarction (AMI). Method: A methodological study that followed the guidelines of the International Council of Nurses and used the Roper, Logan and Tierney Life Activities Model to elaborate the subset. Content validation was performed by 22 specialist nurses. Outcome: Of the 44 diagnoses / results elaborated, 77.27% reached Content Validity Index (CVI) ≥ 0.80 and of the 128 interventions proposed, 44.53% reached CVI ≥ 0.80. At the end, the subset consisted of 34 diagnoses / results and 68 nursing interventions.